Pose Planning of Quadruped Pipe Wall-climbing Robot During Circumferential Motion - Tie Zhang; Jiaoren Wu; Di Cai; Lingfeng Wu (Jixie chuandong)
In order to realize the continuous circumferential motion of the quadruped robot along the inner wall of the pipe，the plan of position and posture during the motion is carried out. Firstly，the pipeline coordinate system and the robot position and posture equations are established，and a circumferential motion including foot posture adjustment，body rotation and body translation is planned. In order to ensure the continuity of the circumferential motion，the angle，direction and displacement of the posture during the motion are planned，and the circumferential motion posture planning is realized through foot motion. Use the joint angle curve of the circumferential motion calculated by Matlab to perform wall-climbing experiments with the robot prototype. Finally，the experimental results and the roll angle analysis verify the correctness of the circumferential motion pose planning.